Religion and Development in Africa - Chitando, Ezra; Gunda, Masiiwa Ragies; Togarasei, Lovemore; Kügler, Joachim (University of Bamberg Press., 2020)
What is development? Who defines it? On top of which mountain can anyone stand and proclaim one community/country “developed”, while characterising another community/country as “un/under-developed”? What, if any, is the relationship between religion and development in Africa? Does religion contribute to development or underdevelopment in Africa? These and related questions elicit quite charged reactions in African studies, development studies, political science and related fields. Africa’sown history, including the memory of marginalisation, slavery and exploitation by global powers ensures that virtually every discussion on development is characterised by a lot of emotions and conflicting views. This is because the majority of the citizens of Africa continue to struggle to access the basics in life.
Keywords: Development, Religion, Africa, World Christianity, African Religions, Gender Studies